30 years of the Lakes Nyos and Monoun gas disasters: A scientific, technological, institutional and social adventure. (February 2019) - Tanyileke, Gregory; Ntchantcho, Romaric; Fantong, Wilson Yetoh; Aka, Festus Tongwa; Hell, Joseph Victor
Abstract: The gas explosions of the mid 80's at Lakes Monoun and Nyos in Cameroon released huge quantities of magmatic CO2 gas that asphyxiated close to 1800 people and thousands of livestock in the surrounding villages, giving birth to a new type of natural disaster called limnic eruption which, interestingly, is both predictable and preventable. These unique events generated renewed interest in volcanic lake studies across the world, resulting in the creation of new associations such as the International Association of Volcanology and Chemistry of the Earth's Interior (IAVCEI) Commission on Volcanic Lakes (IAVCEI-CVL) and institutional reforms regarding civil protection and disaster management as a whole in Cameroon and beyond. Post scientific studies indicated not just gas buildup in the bottom layers of both lakes, but also identified the potential risk of collapse of the natural dam at the outlet of Lake Nyos. As an introduction to this special issue, this paper revisits these two lakes alongside the other Cameroon Volcanic Line (CVL) maars and appraises the scientific and technological achievements registered, discusses the phenomena of limnic eruption and lake turnover in some other Cameroonian lakes, and highlights the lessons learnt as well as perspectives. Design and test degassing experimentation started at Monoun in 1992 and at Nyos in 1995 and led to full-scale degassing with a single pipe at Nyos in January 2001 and at Monoun in 2003. Two more pipes were installed at Monoun in 2006 and at Nyos in 2011 so as to accelerate the degassing, which worked well and rendered the lakes safe by decreasing their CO2 contents to inoffensive levels. Moreover, the much dreaded potential risk of dam collapse and downstream flooding at Nyos has also been averted following the success of dam reinforcement works. In view of these achievements, the science underlying gas accumulation in lakes and subsequent similar catastrophic phenomenon is now understood. Lakes Nyos and Monoun are today infamous and have, over the past 30 years, not only attracted considerable scientific interest and media coverage but have above all, become natural laboratories for capacity development (design and testing of new investigation methods and equipment) and capacity building (infrastructural and human) which were largely boosted under a 5-year joint Japan Cameroon cooperation project code named 'Satreps NyMo'.